2017
DOI: 10.1186/s12864-017-3715-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the accuracy of genomic selection for growth and wood quality traits in an advanced-breeding population of black spruce (Picea mariana)

Abstract: BackgroundGenomic selection (GS) uses information from genomic signatures consisting of thousands of genetic markers to predict complex traits. As such, GS represents a promising approach to accelerate tree breeding, which is especially relevant for the genetic improvement of boreal conifers characterized by long breeding cycles. In the present study, we tested GS in an advanced-breeding population of the boreal black spruce (Picea mariana [Mill.] BSP) for growth and wood quality traits, and concurrently exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
111
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 64 publications
(133 reference statements)
20
111
7
Order By: Relevance
“…We found that the accuracy improved from the TS/VS ratios of 1:1 to 3:1, but accuracy only improved a little after the TS/VS ratio of 3:1. This is different from other studies [4,14] that increased ratio of the TS/VS beyond 3:1 still increase the accuracy. However, we found that our result concurs with other reports when the ratio of TS/VS is related to the number of trees per family [14].…”
Section: The Effect Of Training Data Set and Number Of Trees Per Famicontrasting
confidence: 99%
See 3 more Smart Citations
“…We found that the accuracy improved from the TS/VS ratios of 1:1 to 3:1, but accuracy only improved a little after the TS/VS ratio of 3:1. This is different from other studies [4,14] that increased ratio of the TS/VS beyond 3:1 still increase the accuracy. However, we found that our result concurs with other reports when the ratio of TS/VS is related to the number of trees per family [14].…”
Section: The Effect Of Training Data Set and Number Of Trees Per Famicontrasting
confidence: 99%
“…5). Similar results were obtained by other studies [11,14,41,49]. However, the relative efficiency between ABLUP and GBLUP (the accuracy ratio) is more or less similar in both full-sib and half-sib populations, which indicates that GS could be used in both half-sib and full-sib populations.…”
Section: Effect Of Different Family Structuresupporting
confidence: 88%
See 2 more Smart Citations
“…The best subset of features contains the least number of dimensions that most contribute to prediction accuracy(Guyon et al, 2003). Several studies(Bermingham et al, 2015, Li et al, 2018, and Lenz et al, 2017 have performed marker selection by selecting most significant SNPs through the result of a genome-wide association study (GWAS) or marker effect analysis, but selecting a marker in this way only considers the relationship between the marker and the trait, not the correlation among the markers.…”
mentioning
confidence: 99%